Awareness and Use of Electronic Resources by Undergraduate Students at Kabale University, Uganda - Iroroeavwo Edwin, Achugbue; Benjamin, Ahimbisibwe (Islamic University Multidisciplinary Journal, 2020)
The paper focused on the awareness and use of electronic resources by undergraduate students at Kabale University. It discusses the importance of electronic resources and types of electronic resources; survey research design was adopted for the study and the instrument used for data collection was questionnaire. The target population of this study comprises 2, 600 undergraduate’s students who are duly registered at Kabale University library for the 2018/2019 academic session. A total of 475 of the total population were drawn using a random sampling technique. 475 questionnaires were distributed to the respondents and a total of 469 was duly completed and found usable, which gave 99% response rate. The data collected for this study was analyzed using simple percentage and frequency counts. The study revealed that electronic resources have tremendous impacts on the undergraduate’s students in the course of their academic pursuit. The study also revealed that majority of the respondents makes use of electronic resources on a weekly basis. However, the major challenge undergraduates face with the use of electronic resources is lack of adequate training, followed by lack of expert help while some others complained of slow internet connectivity.